Distancing socially [videorecording (DVD)] - Blake, Chris; Blake, Chris; Levy, Sarah, 1986-; Tudyk, Alan; Paolo, Connor, 1990-; Buckley, Andy, 1965-; O'Heir, Jim, 1962- (Cinedigm, 2021)
Composed of a series of comical vignettes that share a telecommunications application as a common thread, this focuses on loosely connected human interactions taking place virtually across a world in lockdown.